Public Relations Strategy in Improving the Branding Image of Educational Institutions - Siti Norfaizah; Abdul Haq; Khoirul Ulum; Ingrid Solheim (CV Edujavare Publishing, 2026)
In the era of digitalization and globalization, educational institutions face significant challenges in building and maintaining a positive branding image in the public eye. The branding image of educational institutions particularly Islamic institutions plays a crucial role in shaping public perception, which in turn influences public acceptance, the improvement of educational quality, and the active participation of various stakeholders. This study aims to explore the role of public relations (PR) strategies in enhancing the branding image of Islamic educational institutions. The method used in this research is library research, by reviewing various relevant literature sources related to public relations, branding image, and their application within the context of Islamic education. The findings indicate that integrated and consistent communication strategies are essential in establishing a credible and positive institutional image. Additionally, the use of social media, the management of social and religious activities, and alumni engagement also contribute significantly to strengthening the branding image of Islamic educational institutions. This study offers a new perspective in understanding the role of public relations in managing the branding image of Islamic educational institutions, with the hope of providing valuable insights for the development of Islamic educational management and institutional communication in the future.